Multiculturalism, Living Qur’an Islamic Objectives: Muhammadiyah’s Portrait In West Papua - Firdaus, Muhammad Adnan; Abdurahman, Dudung; Muri Salampessy, Yusuf; Rasid, Ruslan (CV. Inara, 2021)
Abstract The topic of Multiculturalism Living Quran Muhammadiyah Papua and Application of Islamic Objectification Theory Kuntowijoyo intends to highlight the application of Da'wah bil regards Persyarikatan Muhammadiyah West Papua. Where is the application of da'wah bil hal Muhammadiyah West Papua by pioneering educational institutions from kindergarten to college, religious institutions such as mosques, pesantren, taklim assemblies, missionary corps and so on. Social institutions such as orphanages. Economic institutions such as Baitul Maal wa Attamwil (BMT). Philanthropic institutions such as Lazis Muhammadiyah. Health institutions such as clinics, and others. In the opinion of the author, once again, is the application of da'wah bil hal. Where the da'wah bil thing is the Muhammadiyah pattern in general and the West Papua Muhammadiyah pattern, according to the author, is the application of Kuntowijoyo's social theory of objectification of Islam. Plus, because of the existence of Muhammadiyah West Papua in the Muslim Minority zone, this is also an application of the application of da'wah bil things that is unique in the frame of multi-culturalism and mainstreaming religious moderation. Keyword: Multiculturalism, Living Qur'an, Muhammadiyah West Papua, Islamic Objectification .